Apophasis and System. Dogmatic Theology in Apophatic Perspective - Woźniak, Robert (Verbum Vitae, 2023)
The subject of the article is the nature of theological apophasis in relation to the systematic aspirations of theological reflection. This relationship is analyzed from the perspective of the three essential truths of Christianity that form the hard core of its message: the Trinity, the personal union of the two natures in Christ, and deification. Accordingly, Trinitarian theology, Christology and anthropology are characterized, each area separately and in relation to the others, by a high degree of systematization. They constitute compact, organic and interrelated theological systems which, as constituent parts, form an organic whole. All three contain significant apophatic themes. An analysis of the connection between their systematicity and their apophatic dimension allows us to draw broader and more general conclusions about apophaticism in general and its place in theological systematization.